Multicultural Based Character Education at The Tebuireng Jombang Islamic Boarding School - Saihul Atho Alaul Huda; Anggi Septa Mujahadah (LPPM Universitas KH. A. Wahab Hasbullah, 2021)
Indonesia as a country that has a wide range of cultural, ethnic, religious and economic backgrounds are different, plurality on the one hand provide the social power, but on the other hand is a challenge when it is not properly managed. Islamic boarding school as an educational institution that has a history of nation-building in Indonesia, of course can be a forum in implementing multicultural education in the face of diversity. This paper describes the multicultural education at Islamic boarding school as a strategy to fostering the social soul in diversity. In its implementation does not distinguish from each other ranging from groups such as gender, ethnicity, race, culture, social background through treatment. Multicultural education has been stressed to the students in order to develop the potential and capacity to the maximum as it requires no special space in themselves and their environtment. This study uses data collection techniques with interviews and documentation methods. The results of this study indicate that the Tebuireng Islamic Boarding School has implemented multicultural education. These activities include a study of the book of adab alim wal muta’allim, ORDA (Regional organization in Islamic boarding schools), basic characters in Tebuireng Islamic Boarding Schools, the culture of queuing for students, attitudes of Tebuireng Islamic Boarding Schools towards non-Muslims, and tawadhu attitudes of students towards non-Muslim guests.